2021
DOI: 10.1002/tax.12649
|View full text |Cite
|
Sign up to set email alerts
|

Global phylogeny and taxonomic reassessment of the lichen genusDendriscosticta(Ascomycota: Peltigerales)

Abstract: The genus Dendriscosticta (Ascomycota: Peltigerales) encompasses several distinctive lichen-forming fungal species restricted to the Northern Hemisphere. Most are flagship species of old-growth forests with good air quality. A global phylogeny of the genus based on multilocus sequence data (ITS, RPB1, EF-1α, MCM7), model-based phylogenetic methods, and morphological and chemical assessments, reveals a high level of cryptic speciation often associated with restricted geographical distribution and/or chemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 94 publications
0
3
0
1
Order By: Relevance
“…Blom & Tønsberg mycobionts were confirmed by BLAST analyses against the GenBank database. Significant matches of 99% identity and 100% coverage were obtained with R. virens from the United Kingdom (KX385135-KX385141) detected by Cornejo et al [ 67 ], and from Norway, detected by Simon et al [ 68 ]. The aligned fungal ITS was 306 bp.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Blom & Tønsberg mycobionts were confirmed by BLAST analyses against the GenBank database. Significant matches of 99% identity and 100% coverage were obtained with R. virens from the United Kingdom (KX385135-KX385141) detected by Cornejo et al [ 67 ], and from Norway, detected by Simon et al [ 68 ]. The aligned fungal ITS was 306 bp.…”
Section: Resultsmentioning
confidence: 85%
“…Tripartite lichen thalli represent interesting models to analyse the different strategies and adaptations resulting from the interactions of the lichen symbionts [ 69 ]. In Lobaria pulmonaria , a coexistence consisting of a mycobiont, photosynthetic green alga ( Symbiochloris reticulata ) and Nostoc cyanobiont is well known [ 13 , 29 , 32 , 67 , 68 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…КК РФ -4, КК РК -1. Реликтовый вид с дизъюнктивным ареалом [Simon et al, 2022]. Находится на северной границе распространения.…”
Section: лишайники (Lichens)unclassified
“…Previous research has shown that taxa in the Ascomycota (e.g. members of the orders Helotiales, Capnodiales, Peltigerales and Verrucariales, among others) are commonly found in symbiotic relationships with algae forming lichens [24][25][26][27][28]. For example, Cladosporium associates with red algae (Porphyra yezoensis) [29] and marine brown algae (Actinotrichia fragilis) [30] to form lichens.…”
mentioning
confidence: 99%